Social Welfare Factors during Covid-19 in Indonesia in 2020-2021 - Aulia Ilma Rachmah; Dwi Prasetyani; Bhimo Rizky Samudro (Universitas Muhammadiyah Ponorogo, 2023)
In general, the progress made by the state has the same goal of improving the welfare conditions of its citizens. An increase in the well-being of people in a region can be seen in the increase in wages received by that region. Unfortunately, at the end of 2019, in December to be exact, a catastrophe believed to be caused by an unknown pneumonia shook the world. The incident occurred in Wuhan, China. China recognized pneumonia as a separate novel coronavirus strain on January 7, 2020. The research method used is qualitative with panel data regression analysis using the 2020-2021 time series and cross-sections of her 34 provinces in Indonesia. The dependent variable in this study is average consumption, and independent variables include gross domestic product (GDP), average wages, number of poor people, and open unemployment rate (TPT). The results of this study are that several independent variables are relevant, the variable GDPP has a positive effect on median consumption, median wages have no effect on median consumption, the number of poor people has a negative effect on median consumption, and TPT has a positive effect on median consumption.